Propanil-Induced Neurotoxicity In Freshwater Common Carp (Cyprinus Carpio) (Applied Biological Research, 2016)
Herbicides are known to affect the metabolic parameters in fishes. For this  reason a study was designed to assess the effects of herbicide propanil (3',4'- dichloropropionanilide) on common carp (Cyprinus carpio L.) through  antioxidant indices and other neurotoxicological parameters. Fishes were  exposed to two concentration of propanil (2 and 4 mg L-1) for 6 and 48 h and effects on neurtoxicity biomarkers [acetylcholinesterase (AChE), Na+/K+- ATPase] and oxidative stress parameters [reduced glutathione levels, superoxide dismutase, catalase, thiobarbituric acid reactive substances and  protein oxidation (protein carbonyl) were studied. Study revealed that  propanil exposure disturbed antioxidant status, increased lipid peroxidation  and protein carbonyl levels in fishes at both doses. Activity of neurotoxicity  enzymes AChE and Na+/K+-ATPase was inhibited at both the doses of  propanil exposure. Propanil was more toxic at higher doses at both the  lengths of exposure.
Keywords: Antioxidant; Cyprinus carpio; herbicide; neurotransmitter; propanil